Integrating media into the classroom - Cambridge Educational ([Lawrenceville, N.J.] : Cambridge Educational, 2005)
In this inspiring and informative two-part series, educators and media specialists with first-hand experience of the challenges and rewards of integrating media into the classroom share their in-depth knowledge. These DVD's helps to gain insight into how we can use technology to improve our lessons, create o more constructivist learning atmosphere, increase student understanding and retention, and motivate students to learn as never before
Practice and case studies (29 min.) -- Theory and research (27 min.)
DVD Format
Keywords: Media programs (Education); Interactive multimedia; Instructional systems -- Design